Effect of Metal Ions on the Flame Retardation of Phosphorylated Cotton Cellulose - DAHIYA, J.B.; RANA, SUSHILA; KUMAR, KRISHAN (Asian Journal of Chemistry, 2010)
This work focuses on the development of durable flameretarded chemically modified cotton cellulose. Cellulose thiophosphordicarbamidate (CTPC) and its complexes with metals such as chromium and iron have been synthesized and characterized. The thermal oxidative degradation and potential flame retardancy was evaluated from thermogravimetric, differential scanning calorimetery analyses and char yield. From the resulting data of TG curve using Broido method, the activation energies of CTPC and metal complexes (24-41 kJ mol-1) for decomposition process are found lower than that of cellulose (165.85 kJ mol-1) in static air. It has also seen that metals have stabilized the CTPC after 350 ºC due to cross-linking and aromatization of residue. The FTIR spectra of chars of modified cellulose indicate that catalyzed dehydration takes place. Modified cellulose samples, when heated, give rise to high char yields. The values of ΔH have also been found reduced and spread in wide range of temperature significantly on introducing phosphorus, nitrogen, sulphur and metals in cellulose. This indicates that the combustibility of modified cellulose is reduced.